Study of the impact of the area on sesame production in Sudan compared to the Arab countries in the period 2008- 2015 - Kenani, M. Mahmoud (Journal of agricultural, environmental and veterinary sciences, 2019)
The study aimed to demonstrate the impact of the area on sesame production in Sudan compared to the Arab countries in the period (2008- 2015), used the descriptive study to identify cultivated areas and production of sesame in Sudan, and the historical approach to follow the development of space, production and curriculum Statistical and Excel data and information analysis program. Data and information were collected from official secondary sources, especially reports and private sources of books and articles. The study concluded for a range of results, that the Sudan achieved the largest cultivated area of sesame crop in the period (2008- 2012) reached 1550.89 thousand hectares and the largest production of sesame in the amount of 295.8 thousand tons/ha then the area rose in 2013 by%66.31, and the production increased by%90, while the area was decreased in 2014 by%53.62, the production was also lower by%69.57, and the area remained at the same level in 2015. While production increased by%19.9, the study made a series of recommendations, including the importance of supporting and developing sesame production in Sudan through the adoption of economic and agricultural policies encouraging investment and stimulating the product and encouraging scientific research, introduction of sesame crop cultivation in the agricultural cycle of government projects Irrigated. Established a typical integrated Sesame production project for manufacturing and marketing to achieve self- sufficiency of plant oils, provide raw material for oil factories and support agricultural exports and balance of payments.
Keywords: area; production; Sesame; Sudan